Cellular networks controlling Th2 polarization in allergy and immunity - Kool, Mirjam (Faculty of 1000 Ltd, 2012)
In contrast to the development of Th1 (type 1 T helper cells), Th17 and Treg (regulatory T cells), little is known of the mechanisms governing Th2 development, which is important for immunity to helminths and for us to understand the pathogenesis of allergy. A picture is emerging in which mucosal epithelial cells instruct dendritic cells to promote Th2 responses in the absence of IL-12 (interleukin 12) production and provide instruction through thymic stromal lymphopoieitin (TSLP) or granulocyte-macrophage colony stimulating factor (GM-CSF). At the same time, allergens, helminths and chemical adjuvants elicit the response of innate immune cells like basophils, which provide more polarizing cytokines and IL-4 and reinforce Th2 immunity. This unique communication between cells will only be fully appreciated if we study Th2 immunity in vivo and in a tissue-specific context, and can only be fully understood if we compare several models of Th2 immune response induction.